PERAN AUDIT INTERNAL TERHADAP PELAKSANAAN GOOD GOVERNANCE DI PERBANKAN SYARIAH - Ardi, Muhammad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: Law 17 of 2003 and Law 1 Year 2004 triggered the renewal of state financial management. From both laws, the government through the Public Service Agency implements good governance in order to improve the performance and service of the community. This paper aims to examine the effect of internal audit for good governance either partially or simultaneously. Internal audits have a positive and significant impact on good governance both partially and simultaneously, indicating that both internal audits can improve the creation of good governance